Growth Dynamics : The Myth of Economic Recovery - Saxena, Sweta (IMF Working Papers; Working Paper ;, 2005)
Using panel data for a large number of countries, we find that economic contractions are not followed by offsetting fast recoveries. Trend output lost is not regained, on average. Wars, crises, and other negative shocks lead to absolute divergence and lower long-run growth, whereas we find absolute convergence in expansions. The output costs of political and financial crises are permanent on average and long-term growth is negatively linked to volatility. These results also imply that panel data studies can help identify the sources of growth and that economic models should be capable of explaining growth and fluctuations within the same framework.